Isolation and identification of Trichoderma sp. in vegetables soils at Jeli,Kelantan - Siti Aminah Mohamed Zaini (2016)
Recently, the use of biological control agents (BCAs) has improved the disease resistance in agricultural crops. In this present study was investigated to isolate Trichoderma sp. from vegetable soils at Jeli, Kelantan. Before collect the soil sample, the land was divided into two sites of site A and site B. The soil sample was collected and Trichoderma sp. was incestigate from these two sites. There are many types of microbial colony such as bacteria, fungal, and yeast colonies were found from the soil.While this study aim to identify Trichoderma sp., thus further study was carried out to find Trichoderma colony only. A total of three Trichoderma colony were isolate from the vegetables soils in Jeli, Kelantan. These isolates were identified and characterized by macro- and micromorphological characteristics of Trichoderma. The morphological characteristics measured by the colony appearance, growth rate on Potato Dextrose Agar (PDA), Dichloran Rose Bengal Chloramphenicol (DRBC) and Trichoderma Selective Medium (TSM). The micromorphological characteristics were earned out based on the shapes and sizes of conidia, the branching pattern of conidiophore and production of chlamydospores. All three Trichoderma colony was identified as Trichoderma harzianum. The three Trichoderma harzianum species coded as THJVT1, THJVT2, and THJVT3. The isolated three strains of Trichoderma harzianum were tested as antagonistic activity (in term of biocontrol agents) against Fusarium oxysporum (a causal pathogen for panama disease in banana plant). The percentage inhibition of radial growth (PIRG) data analysis was used to find Trichoderma antagonistic activity determination. Among these Trichoderma isolates, the strain THJVT3 showed the highest potential as a biological control agent which is 57.26% because it showed the highest antagonistic activity against F.oxysporum. The other two isolates, THJVT1 and THJVT2 also have ability to inhibit the mycelial growth of F.oxysporum with at least 53.74% and 54.70% respectively. Finally, all three straints have the antagonistic activity against Fusarium oxysporum, with that strain THJVT3 might be the most promising Trichoderma strain in Biocontrol Program for management of Panama disease in Banana.